Impact of regular whole-blood donation on hemoglobin level - Supri Hartini; I Gede Andika Sukarya; Malika Sasi Fitria Fortuna (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Blood donation is regarded as a noble, voluntary act that is done without compensation. Prior to donation, donors undergo a preliminary examination (including blood pressure, blood type, hemoglobin levels, pulse, etc.). After donating blood, it is important to recheck their hemoglobin levels to determine whether they are low or remain stable. Purpose: To determine the impact of regular whole blood donation on hemoglobin levels. Method: A descriptive study with an observational design. The variable is the hemoglobin level before and after blood donation. The research was conducted at the Indonesian Red Cross Society of Tenggarong, with 45 blood donors as respondents. Hemoglobin levels were measured using a POCT (Point of Care Testing) tool. Data analysis was performed univariately to assess the hemoglobin level changes before and after donation. Results: The study revealed gender characteristics for male and female donors, with an average Hb level of 14.5 gr/dl for men and 13.25 gr/dl for women in their last donation. For current donation, the average Hb levels were 14 gr/dl for men and 11.65 gr/dl for women. The decrease in hemoglobin levels was 0.5 gr/dl for men and 1.6 gr/dl for women. Almost all donors showed no symptoms post-donation. Conclusion: Hemoglobin levels decreased after donation, but there were no symptoms such as fainting for both men and women. Suggestion: Donors can use this information to increase their understanding of hemoglobin levels, ensure they get adequate rest the night before donation, eat iron-rich foods, and avoid strenuous activities after donating blood. It is also recommended that future researchers consider including the menstrual cycle as a factor in similar studies.